Partially unraveling mechanistic underpinning and weight loss effects of time-restricted eating across diverse adult populations: A systematic review and meta-analyses of prospective studies. - Duc Tran Quang; Nguyen Di Khanh; Linh Le Cu; Huyen Nguyen Thi Hoa; Chi Vu Thi Quynh; Quang Phan Ngoc; Thuy Bui Thi (PLoS ONE)
Time-restricted eating (TRE) is a promising and cost-effective dietary approach for weight management. This study aimed to evaluate the effects of TRE on weight loss in three adult populations using pre- and post-intervention analyses while also investigating its underlying mechanism. A systematic search was conducted across four databases (PubMed, Web of Science, Scopus, and the CENTRAL) up until January 28, 2024, specifically focusing on prospective studies that examined the efficacy of TRE in achieving weight loss. A random effects model was employed to conduct meta-analyses, while heterogeneity was assessed using the I2 statistic (PROSPERO: CRD42023439317). The study encompassed 36 selected studies involving 44 effect sizes and 914 participants. The effectiveness of the TRE was found to vary across health conditions, with modest weight loss observed in healthy individuals (pooled effect size -1.04 Kg, 95% CI: -1.42 to -0.65) and more significant weight reduction seen in participants with chronic diseases (pooled effect size -3.33 Kg, 95% CI: -5.05 to -1.62) and overweight/obesity (pooled effect size -4.21 Kg, 95% CI: -5.23 to -3.10). The observed decrease in body weight could be partially attributed to factors influencing energy balance, as evidenced by the significantly lower mean calorie intake at the end of the intervention (1694.71 kcal/day, 95% CI: 1498.57-1890.85) compared to the baseline intake (2000.64 kcal/day, 95% CI: 1830-2172.98), despite the absence of intentional efforts to restrict energy intake by the participants. These findings support the efficacy of this lifestyle intervention for weight loss maintenance and guide the development of its clinical guidelines.